Técnicas motivacionales y conductas disruptivas en el aprendizaje de los estudiantes del sexto A en la Unidad Educativa Adolfo Valarezo, Loja 2022-2023 - Cango Salinas, Gabriela Briggette (2023)
Motivational techniques are a favorable alternative within education, since it allows students to be predisposed to develop all the activities planned by their teacher and in turn have favorable environments to carry out the educational process, on the other hand, it allows reduce disruptive behaviors that students present during class hours, the same ones that hinder a favorable and conducive environment for learning; that is why the following research was carried out, whose general objective was to determine the importance of motivation and the influence of disruptive behaviors on learning in the students of the sixth grade A of the “Adolfo Valarezo” educational unit in the city of Loja; the current study was descriptive, with a mixed approach (quali-quantitative) that also maintained a non-experimental design, the technique used was observation (applied to the students) and the survey (applied to the teacher), the test as an instrument (applied to students), sampling was the students of the Sixth grade A of the educational center, in turn establishing in this way the validity of the current investigative work which is relevant in the academic field, because its results generated a favorable impart in the students and teachers, obtaining adequate learning and at the same time making it interactive and motivating by creating dynamic environments. In conclusion, motivational techniques are an ideal outlet for the teacher, but it is essential to know how and when to apply them, so that they have a relevant influence. Keywords: Motivational techniques - Disruptive behaviors - Favorable environment - Significant learning.